Multicyclic sediment transfer along and across convergent plate boundaries (Barbados, Lesser Antilles). (13th January 2015) - Limonta, Mara; Garzanti, Eduardo; Resentini, Alberto; Andò, Sergio; Boni, Maria; Bechstädt, Thilo
Abstract: The main source of siliciclastic sediment in the Barbados accretionary prism is off‐scraped quartzose to feldspatho‐litho‐quartzose metasedimentaclastic turbidites, ultimately supplied from South America chiefly via the Orinoco fluvio‐deltaic system. Modern sand on Barbados island is either quartzose with depleted heavy‐mineral suites recycled from Cenozoic turbidites and including epidote, zircon, tourmaline, andalusite, garnet, staurolite and chloritoid, or calcareous and derived from Pleistocene coral reefs. The ubiquitous occurrence of clinopyroxene and hypersthene, associated with green‐brown kaersutitic hornblende in the north or olivine in the south, points to reworking of ash‐fall tephra erupted from andesitic (St Lucia) and basaltic (St Vincent) volcanic centres in the Lesser Antilles arc. Modern sediments on Barbados island and those shed by larger accretionary prisms such as the Indo‐Burman Ranges and Andaman‐Nicobar Ridge define the distinctive mineralogical signature of Subduction Complex Provenance, which is invariably composite. Detritus recycled from accreted turbidites and oceanic mudrocks is mixed in various proportions with detritus from the adjacent volcanic arc or carbonate reefs widely developed at tropical latitudes. Ophiolitic detritus, locally prominent on the Andaman Islands, is absent on Barbados, where the prism formed above a westward subduction zone with a shallow décollement plane. The four‐dimensional complexities inherent with multicyclic sediment dispersal along and across convergent plate boundaries require quantitative provenance analysis as a basic tool in paleogeographic reconstructions. Such analysis provides the link between faraway factories of detritus and depositional sinks, as well as clues on subduction geometry and the nature of associated growing orogenic belts, and even information on climate, atmospheric circulation and weathering intensity in source regions.